Thyroid Storm Triggered by Strangulation in a Patient with Undiagnosed Graves’ Disease - Jorge I. Conte; Marilyn A. Arosemena; Kunal Kapoor; Naomi G. Dempsey; Megan L. Zaleski; Atil Y. Kargi (Case Reports in Endocrinology)
Thyroid storm is the life-threatening end-organ manifestation of severe thyrotoxicosis. If left untreated, thyroid storm may cause acute heart failure, multiorgan dysfunction, and death. A high degree of suspicion is necessary to make the diagnosis and start antithyroid medications to decrease mortality. Thyroid storm is generally seen in patients with Graves’ disease but should also be suspected in patients with fever, tachycardia, altered mental status, and risk factors including local trauma to the neck, such as strangulation. Based on our review, we report the first case of thyroid storm after strangulation as the presentation of previously undiagnosed Graves’ disease.